Identidade territorial do descendente tirolês em Santa Leopoldina–ES - Amorim, Mariana Pereira de (2018)
The paper studies the territorial identity of descendants of Tyrolean immigrants, set in a rural territory. The concrete object is the Tyrolean community, located in the interior of the municipality of Santa Leopoldina, central region of the state of Espí